ACTION RESEARCH ON STUDENTS’ CREATIVE INVENTIONS IN VOCATIONAL HIGH SCHOOL - Kuo, Cheng; Chen, Fei (PEOPLE: International Journal of Social Sciences, 2020)
Because the bicycle lacks lighting equipment, there is no indicator light when steering and braking, thus making it is easy to cause a rear vehicle collision and form a casualty, especially at night. In view of this, this study focused on the safety of bicycles at night, taking vocational high school students, using the existing equipment of the school, combined with relevant curriculum theory and practice, creative thinking and production of "Bicycle safety display device", the LED projection lamp installed in the back seat, with the back of the bicycle rider as the projection screen, can display the enlarged pattern of left and right turn and brake, so that the rear vehicle can be clearly identified to reduce the incidence of accidents. The conclusions of this study are as follows:(1)The study found that the production of the "Bicycle Safety Display Device" enhanced students’ understanding and application of relevant courses; (2) The study found that the production of "Bicycle Safety Display Device" enhanced the student’s circuit design and production capabilities; (3) Through participation in the project, the students generally came to believe that the production of the "Bicycle Safety Display Device" can unite the team’s centripetal force and contribute greatly to the improvement of cooperative learning, and problem solving and innovative invention capabilities; (4) The finished product of this study is useful for the night driving safety of the bicycle.